Bioglass promotes wound healing by affecting gap junction connexin 43 mediated endothelial cell behavior. (April 2016) - Li, Haiyan; He, Jin; Yu, Hongfei; Green, Colin R.; Chang, Jiang
Abstract: It is well known that gap junctions play an important role in wound healing, and bioactive glass (BG) has been shown to help healing when applied as a wound dressing. However, the effects of BG on gap junctional communication between cells involved in wound healing is not well understood. We hypothesized that BG may be able to affect gap junction mediated cell behavior to enhance wound healing. Therefore, we set out to investigate the effects of BG on gap junction related behavior of endothelial cells in order to elucidate the mechanisms through which BG is operating. In in vitro studies, BG ion extracts prevented death of human umbilical vein endothelial cells (HUVEC) following hypoxia in a dose dependent manner, possibly through connexin hemichannel modulation. In addition, BG showed stimulatory effects on gap junction communication between HUVECs and upregulated connexin43 (Cx43) expression. Furthermore, BG prompted expression of vascular endothelial growth factor and basic fibroblast growth factor as well as their receptors, and vascular endothelial cadherin in HUVECs, all of which are beneficial for vascularization. In vivo wound healing results showed that the wound closure of full-thickness excisional wounds of rats was accelerated by BG with reduced inflammation during initial stages of healing and stimulated angiogenesis during the proliferation stage. Therefore, BG can stimulate wound healing through affecting gap junctions and gap junction related endothelial cell behaviors, including prevention of endothelial cell death following hypoxia, stimulation of gap junction communication and upregulation of critical vascular growth factors, which contributes to the enhancement of angiogenesis in the wound bed and finally to accelerate wound healing. Although many studies have reported that BG stimulates angiogenesis and wound healing, this work reveals the relationship between BG and gap junction connexin 43 mediated endothelial cell behavior and elucidates one of the possible mechanisms through which BG stimulates wound healing.